Silver nanoparticle-induced impaired autophagic flux and lysosomal dysfunction contribute to the microglia inflammation polarization. (December 2022) - Shang, Mengting; Niu, Shuyan; Chang, Xiaoru; Li, Jiangyan; Zhang, Wenli; Guo, Menghao; Wu, Tianshu; Zhang, Ting; Tang, Meng; Xue, Yuying
Abstract: Silver nanoparticles (AgNPs) have been incorporated in many consumer and biomedical products. Serious concerns have been expressed about the environmental and public health risks caused by nanoparticles. In previous studies, we found that AgNPs induced microglia polarization of the inflammatory phenotype. Autophagy was a critical for AgNPs-induced neuroinflammation. In the present study, we evaluated in detail the effects of AgNPs in different stages of the autophagy process, and we found that AgNPs induced neuroinflammatory responses and autophagic flux blockage both in the mouse brain and BV2 cells. AgNPs inhibited autophagosome-lysosome fusion and impaired the lysosomal functions by reducing the levels of lysosomal-associated membrane proteins, promoting lysosome membrane permeability and altering the lysosomal acidic microenvironment. These changes resulted in the defects in autophagic substrate clearance and subsequently led neuroinflammation. In addition, the elevation of autophagy could prevent the neuroinflammation induced by AgNPs. As a result, AgNPs hindered autophagic flux by inhibiting autophagosome fusion with lysosomes, thus aggravating the AgNPs-induced neurotoxicity. These findings will provide new insights to investigate the molecular mechanisms of neurotoxicity caused by AgNPs. Graphical abstract: Image 1 Highlights: AgNPs induced neuroinflammation and autophagic flux blockage in vivo & in vitro. AgNPs inhibited autophagosome-lysosome fusion and impaired the lysosomal functions. AgNPs hindered autophagic flux thus aggravating the AgNPs-induced neurotoxicity. Autophagy might play a protective role in AgNPs-induced neuroinflammation.